The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1175/1520-0477(1984)065<0138:iostfs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Improved Ocean Surface Temperatures From Space—Comparisons With Drifting Buoys

Abstract: Multi-window infrared measurements, together with visual chanr observations, enable relatively high-resolution and accurate local, regional, and global retrievals of ocean surface temperatures to be repetitively and routinely obtained from operational environmental satellites. Drifting buoys appear to be the best means to date of validating the satellite estimates. Root mean square differences of about 0.6°C are found between satellite and drifter, whereas with ships-ofopportunity they are 1.8°C. Fixed buoy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(57 citation statements)
references
References 1 publication
(2 reference statements)
3
54
0
Order By: Relevance
“…SST was estimated in situ at 1 m depth with our conductivitytemperature-depth (CTD) sensors and more frequently from imagery collected by the advanced very high resolution radiometer (AVHRR) sensors on the NOAA 11, 12, and 14 satellites. The satellite SST were derived using the split window techniques [Walton, 1988;Strong and McClain, 1984;McClain et al, 1983]. While nonlinear algorithms developed for AVHRR data could be used, there is no conclusive evidence that these algorithms are any better than the multichannel sea surface temperature algorithms.…”
Section: Methodsmentioning
confidence: 99%
“…SST was estimated in situ at 1 m depth with our conductivitytemperature-depth (CTD) sensors and more frequently from imagery collected by the advanced very high resolution radiometer (AVHRR) sensors on the NOAA 11, 12, and 14 satellites. The satellite SST were derived using the split window techniques [Walton, 1988;Strong and McClain, 1984;McClain et al, 1983]. While nonlinear algorithms developed for AVHRR data could be used, there is no conclusive evidence that these algorithms are any better than the multichannel sea surface temperature algorithms.…”
Section: Methodsmentioning
confidence: 99%
“…Ocean temperature is measured by using thermal-infrared wavelengths, so the quantity measured is the emitted radiance, i.e., the surface temperature. Multichannel SST estimates were computed from a combination of two ambient temperature channels on the National Oceanographic and Atmospheric Administration's (NOAA's) Advanced Very High Resolution Radiometer (AVHRR) sensor and are archived in that form (9,10). These data were available in weekly composites that were resampled to 18-km global coverage [National Aeronautics and Space Ad- the data had the coarsest spatial resolution of all of the data examined.…”
Section: Datamentioning
confidence: 99%
“…So the average errors indicated for the AVHRR-SST estimates (Llewellyn-Jones et al, 1984;Strong & McClain, 1984;Lee et al, 2005;Parra et been previously reported (Gaiero et al, 2003;Gasso & Stein, 2007). Also, the ash plumes generated by the eruption of two volcanoes in the last five years (Chaitén on May 2008 and Puyehue on June 2011) affected the atmospheric conditions of the study region (Lara, 2009;Okazaki & Heki, 2012).…”
Section: Discussionmentioning
confidence: 59%